(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Medical professionals must have a firm knowledge of medical ethics in order to practice sound medicine. It is a part of our MBBS curriculum and aids in educating future physicians about medical ethics and developing a positive attitude towards them. This study aimed at assessing the knowledge and attitude of 5th year MBBS students of four government and non-government medical colleges of Chattogram towards medical ethics. Materials and methods: A descriptive cross sectional study was done in Chattagram Maa-O-Shishu Hospital Medical College, Chittagong Medical College, BGC Trust Medical College and Marine City Medical College from August 2023 to October 2023. A total of 400 MBBS 5th year students voluntarily participated in this study. A structured questionnaire including knowledge and attitude towards medical ethics was distributed among the students. Five point Likert Scale (Strongly agree, agree, neutral, disagree and strongly disagree) was used to determine the knowledge and attitude towards medical ethics. Percentages and Frequencies were used to assess the knowledge and attitude. Data was analyzed by Statistical Package of Social Sciences version 24. Results: In this study, out of 400 students, 152(38%) were male and 248(62%) were female. The age range of the participants was 22-29 years. The common source of knowledge on medical ethics was lectures (85%) followed by books (71%), internet (31%), seminars (24%), journals (15%) and television (12%). Approximately 377 (94.25%) of students agreed that conduct of the doctor carries utmost importance. Approximately 351 respondents (87.75%) disagreed with the notion that patient secrets can be disclosed. About 295(73.8%) answered that law of Bangladesh does not permit Euthanasia. 384 (96%) were aware that medical ethics is an integral part of their MBBS syllabus and 303(75.8%) knew that their institution has an Institutional Ethical Committee. Conclusion: Undergraduate students in this study had a moderate to good knowledge on medical ethics. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 88-95